The fossil content of the Upper Triassic Molteno Formation, South Africa - Anderson, John M.; Anderson, Heidi M. (Bernard Price Institute for Palaeontological Research, 1984)
The present paper is essentially drawn, with a few additions (the insects in particular) and changes, from the section on the Molteno Formation in the book Prodromus of South African megafloras: Devonian to L. Cretaceous currently in press (Anderson and Anderson 1984). The repetition is justified by the nature and scope of this Haughton Memorial Volume- an attempt to bring together a series of papers giving a general overview of the 'Stormberg Series' (Molteno to Drakensberg formations). We are in the process of preparing a series of volumes on the palaeoflora of the Molteno Formation. These are based primarily on our own collections begun in 1967 and now amounting to 15 500 catalogued slabs from 74 assemblages. The first volume has been published (Anderson and Anderson 1983a) and provides an interim synthesis of the megaflora to species level as well as a detailed taxonomic account of Dicroidium, the dominant most diverse element. For further detail and clarification of aspects of the paper presented here the above mentioned volumes should be consulted.
Keywords: Megaflora; Megaplant; palaeoflora; Stormberg